MADRASAH LEADERSHIP IN IMPROVING THE QUALITY OF STUDENTS IN MAN 2 MODEL MEDAN - Nur Azizah; Candra Wijaya; Muhayya Meutia; Muhammad Fuad Zaini (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The focus of research is: 1) the example of the headmaster of madrasas to teachers, staff and madrasah residents; 2) the head of madrasa in motivating teachers, staff and madrasa citizens; 3) madrasa head in improving the quality of students. The formulation of the problem in this study is how the leadership of the head of state madrasah aliyah in improving the quality of students and the purpose of this study is to find out the leadership of the head of the state madrasa aliyah in improving the quality of students. This type of research is a qualitative research and data collection techniques are observation, interviews and documentation. The results of the study show the leadership of the Madrasah MAN 2 Medan Model as a leader who listens to the opinions and ideas of teachers and madrasa staff who aim to improve the quality of students. The madrasa head gives exemplary values of morality and values of worship to teachers, madrasah staff and residents and the madrasa head gives the example of courtesy in dressing for teachers and students. Efforts to improve the quality of students carried out in madrassas by offering several excellent programs and daily programs. Evaluations conducted by the teacher every day, month and year, this goal is done to see the learning outcomes. AbstrakFokus penelitian merupakan : 1) keteladanan kepala madrasah kepada guru, staf dan warga madrasah; 2) kepal madrasah dalam memotivasi guru, staf dan warga madrasah; 3) kepala madrasah dalam peningkatan mutu peserta didik. Rumusan masalah dalam penelitian ini ialah bagaimana kepemimpinan kepala madrasah aliyah negeri dalam peningkatan mutu peserta didik dan tujuan penelitian ini ialah untuk mengetahui kepemimpinan kepala madrasah aliyah negeri dalam peningkatan mutu peserta didik. Jenis penelitian ini merupakn penelitian kualitatif dan teknik pengumpulan data ialah observasi, wawancara dan dokumentasi. Hasil penelitian menunjukkan kepemimpinan madrasah MAN 2 Model Medan sebagai seorang pemimpin yang mendengarkan pendapat dan ide-ide dari guru dan staf madrasah yang bertujuan untuk peningkatan mutu peserta didik. Kepala madrasah memberikan keteladanan yang bernilai akhlakul karimah dan nilai-nilai ibadah kepada guru, staf dan warga madrasah dan kepala madrasah memberikan keteladana berupa sopan santun dalam berpakaian kepada guru dan peserta didik. Upaya peningkatan mutu peserta didik yang dilakukan di madrasah dengan menawarkan beberapa program unggulan dan program harian. Evaluasi yang dilakukan guru setiap hari, bulan dan tahun, tujuan ini dilakukan untuk melihat hasil pembelajaran.